An Automated Technique for the Measurement of Limb Occlusion Pressure During Blood Flow Restriction Therapy Is Equivalent to Previous Gold Standard - Muhammad J. Abbas, B.S; Malik E. Dancy, M.D; Erick M. Marigi, M.D; Lafi S. Khalil, M.D; Toufic R. Jildeh, M.D; Patrick J. Buckley, B.S; Javair Gillett, M.S; William Burgos, Ph.D; Kelechi R. Okoroha, M.D (Elsevier, 2022)
Purpose: To evaluate the efficacy of an automated pneumatic torniquet pump and its ability to automatically calculate the limb occlusion pressure (LOP), as compared with the manual Doppler ultrasound technique. Methods: Participants presenting to a Sports Medicine clinic were evaluated for study enrollment. Participants were fitted with a pneumatic tourniquet for the upper and lower extremity. LOP measurements were taken with a Doppler ultrasound or automated SmartCuffs PRO device in a randomized order. Results: Final analysis was performed on 96 limbs (48 upper extremities and 48 lower extremities). The study population had a mean age 37.1 ± 14.7 years old and a mean body mass index of 25.47 ± 3.80. The mean measured LOP pressure on the upper extremity with Doppler ultrasound was 174.0 ± 48.7 mm Hg with a range from 120 to 282 mm Hg, whereas the mean measured LOP by the automated pump was 184.0 ± 44.9 mm Hg with a range from 135 to 266 mm Hg. There was no statistically significant difference found between the Doppler LOP and the Smart Cuff upper extremity LOP (P = .29). When evaluating LOP pressure on the lower extremity the mean LOP found with the Doppler ultrasound was 195.0 ± 31.9 mm Hg with a range from 160 to 272 mm Hg, whereas the automated pump the mean LOP was 205.0 ± 27.1 mm Hg with a range from 168 to 278 mm Hg. There was no statistically significant difference found between the Doppler LOP and the automated pump lower extremity LOP (P = .09). Conclusions: No difference in the personalized LOP measurement was found when comparing an automated pump with the current gold standard of manual Doppler ultrasound. No patients companied of pain or discomfort during the LOP measurement. Level of Evidence: Level II, diagnostic: prospective cohort study.